Effect of compound organic trace minerals on growth performance, serum indexes and micromineral excretion in fattening pigs - MA Lianxiang; HOU Chuanchuan; HE Junna; QIU Jialing; LU Xintao; GUO Yang; LIU Bing; LIN Gang; XUE Yan; YU Dongyou (浙江大学学报. 农业与生命科学版)
To investigate the effects of low-dose compound organic trace minerals (Fe, Cu, Mn and Zn) on growth performance, serum trace mineral contents, antioxidative indexes and fecal trace element excretion in fattening pigs with different trace element feeding backgrounds, a total of 192 Duroc×Landrace×Large White pigs with similar body mass [(61.2±4.4) kg] and identical parity were selected and divided into four groups with four replicates each (12 pigs per pen) in a 2×2 factorial design. The first factor was feeding background (background I: commercial dosages of inorganic Fe, Cu, Mn, Zn were fed to suckling pigs, nursery pigs and growing pigs; background O: organic Fe, Cu, Mn, Zn at 50%, 30% and 20% commercial recommended levels were fed to suckling pigs, nursery pigs and growing pigs, respectively), while the second factor was dietary treatment [inorganic trace mineral (ITM): basal diet+inorganic Fe, Cu, Mn, Zn of 100, 20, 25, 100 mg/kg, respectively; organic trace mineral (OTM): basal diet + organic Fe, Cu, Mn, Zn of 20, 4, 5, 20 mg/kg, respectively). The feeding period lasted for 82 days, with 38 days for early finishing stage and 44 days for late finishing stage. The results showed that: 1) The feeding background and dietary treatment both had no significant influences on the growth performance of fattening pigs (P>0.05) during the whole period. 2) The OTM diet increased the Zn content (P<0.05) and Mn-superoxide dismutase (SOD) activity (P=0.05) in the serum of fattening pigs at early finishing stage, and decreased the malonaldehyde (MDA) content (P=0.05). 3) The OTM diet significantly reduced the Fe, Mn, Cu and Zn emissions (P<0.05) in manure during whole phases; while the background O significantly decreased the Fe emission at the early finishing stage and Fe, Cu, Zn emissions at the late finishing stage in manure (P<0.05). The background O and OTM had an interaction (P<0.05) on reducing Fe content in fattening pig manure at the late finishing stage. The above results indicate that the addition of low-dose organic trace minerals in the basal diet can significantly reduce the heavy metal emissions in the fattening pig manure, and improve antioxidant level of growing- fattening pigs without affecting its growth performance; while feeding background at early growth stages can also significantly influence the heavy metal emissions in fattening pigs.